Peningkatan Pelayanan Publik: Pengelolaan Ekowisata Di Daerah Provinsi Yogyakarta Berdasakan Ulasan Sentimen Pengunjung - Iwan Kurniawan (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2024)
The development of ecotourism, especially in the Provinsi Yogyakarta region known for its rich natural and cultural potential, depends on the improvement of public services. The aim of this research is to identify the strengths and weaknesses in the public services provided by destination managers in Provinsi Yogyakarta through visitor sentiment analysis toward ecotourism in the area. Additionally, the purpose of this sentiment analysis is to explore whether visitors have a positive, negative, or neutral impression of these ecotourism attractions and to evaluate tourism management with various strategies for improvement. The research method uses a quantitative approach by collecting secondary data and processing it through sentiment analysis. The research findings show that tourist destinations in Provinsi Yogyakarta receive predominantly positive reviews, with 44 positive reviews compared to 11 negative ones. Beaches, mountains, museums, and temples are the most frequently visited destinations. Therefore, the development strategies should focus more on these four tourist destinations.